Strategi Pelaksanaan Layanan Bimbingan Konseling Berbasis Kurikulum K13 di Madrasah Aliyah Sabrun Jamil Botupingge - Taruna, Ariswan; Posangi, Said Subhan; Pantu, Eka Prastian (STIKes Ibnu Sina Ajibarang, 2025)
The K13 Curriculum-based counseling guidance strategy is an approach in guidance and counseling services that is in line with the principles and structure of the K13 Curriculum. This strategy aims to assist students in achieving optimal development in accordance with the demands of the curriculum, both in academic, personal, social, and career aspects. The research method used is qualitative with data collection techniques through interviews, and documentation. The results of this study show that the strategy for implementing counseling guidance services based on the K13 curriculum at Madrasah Aliyah Sabrun Jamil Botupingge applies individual counseling strategies, consultation, group counseling, group guidance, remedial teaching which aims to help individuals and groups in overcoming difficulties, increasing self-potential, and achieving optimal development in various aspects of life.